Criminalization of Polygamy Without Wife’s Consent from the Perspective of the New Criminal Code (Law No. 1 of 2023) and Maqashid Sharia - Sunida; AdangJumhurSalikin (Jurnal Ragam Pengabdian, 2026)
This study analyzes the legal implications of polygamy, which are considered criminal acts, for those who practice polygamy without the permission of the legal wife or a court ruling, based on Law No. 1 of 2023 (the New Criminal Code), andacritical reviewbasedontheMaqashidSyariah analysis.In2026, the implementation of the New Criminal Code affirms the legal position of polygamous marriages carried out in violation of existing procedures and without the permission of the legal wife, as determined by a Religious Court Decree. The research method used is a juridical-normative legal research method with a statutory and conceptual analysis approach. The results of the study indicate that Articles 402 and 403 of the New Criminal Code prohibit polygamy without the permission of the legal wife and Marriage without a courtrulingiscategorizedasacriminaloffensewithamaximumpenaltyofsix years' imprisonment or a Category IV fine. From a sociological and juridical perspective, this legal provision constitutes a complaint offense aimed at protecting the rights of the first wife. From the perspective of Maqashid Syariah (Islamic Law), the application of this criminal sanction is seen as aligned with the principle of public welfare (mashlahah), particularly in safeguardingoffspring(hifzhunnasl)toensurethelegalstatusofchildren,and safeguarding property (hifzhul maal) related to inheritance rights and maintenance. Criminal sanctions serve as a legal instrument to prevent harm neglect and ensure that the principle of justice, an absolute requirement for polygamy in Islam, is fulfilled both administratively and substantively in a marriage.